ETHNOIMMIGRATION: COMPARATIVE ANALYSIS - K. C. Dallakyan (Научный вестник МГТУ ГА, 2016)
The article deals with the analysis of ethnic immigration, the factors influencing the process of ethnos migration have been determined, objective and subjective components of this process have been singled out. It is for the first time that the author treals ethnoimmigration as an independent form in the migration stream.